THE EFFECT OF NON PERFORMING FINANCING, FINANCING TO DEPOSIT RATIO AND OPERATING EXPENSE TO OPERATING INCOME RATIO (BOPO) TO PROFITABILITY - Sri Suartini; Hari Sulistiyo; Wahyuni Indrianti (AFEBI Economic and Finance Review, 2018)
The issues raised in this study are: to determine, explain and analyze profitability, Non Perfroming Loan, Financing to Deposit Ratio and Operating Expense to Operating Income in Bank of sharia and the partial effect and simultaneous of NPF, FDR and Operating Expense to Operating Income ratio  to Profitability Bank of sharia Period 2014 -2016.The number of samples taken 12 Bank of sharia in the study period with saturated sampling technique. This research expected to contribute and to the development of the field of accounting, especially financial accounting. The research methods used by the author in this study, using descriptive and verification, the results showed conclusions are: NPF has no effect on profitability because of the results of calculations performed tcount smaller than ttabel. FDR has not effect on profitability because of the results of calculations performed tcount smaller than ttabel. Partially Operating Expense to Operating Income has significant negative effect on profitability. Operating Expense to Operating Income is the most influential variable among other variables on profitability. The effect of simultaneous NPF, FDR and Operating Expense to Operating Income on profitability  of 75.8% while the remaining 24.2% is the influence of other factors not examined. We can conclude that NPF, FDR and ROA simultaneously positive and significant impact on profitability Bank of sharia in the study period.JEL Classification: G10, G12, G21Keywords: FDR, NPF, Profitability, ROA